The Influence of Green Perceived Quality, Green Perceived Risk, and Green Brand Image on Green Satisfaction - Anggita Cahyani Hidayah; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2026)
The rapid growth of Indonesia's skincare industry and rising environmental awareness have increased demand for green skincare products, making consumer satisfaction essential for market competitiveness. This study aims to examine the effects of green perceived quality, green perceived risk, and green brand image on green satisfaction among consumers of Sensatia Botanicals green skincare products in Yogyakarta. This study adopted a quantitative explanatory research design based on primary data obtained through questionnaire surveys administered to 100 respondents selected using purposive sampling. The collected data were processed through analytical procedures, including validity and reliability assessments, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination. The results demonstrate that green perceived quality exerts a positive and statistically significant influence on green satisfaction. In contrast, green perceived risk shows a negative and significant effect on green satisfaction, whereas green brand image contributes positively and significantly to green satisfaction. Furthermore, the three independent variables collectively explain 81.7% of the variance in green satisfaction. These findings indicate that improving product quality, minimizing consumers’ perceived risk, and strengthening a brand’s environmental image are essential strategies for enhancing green satisfaction and sustaining competitiveness in the green skincare industry.